How to Be a Function Pluralist. (10th July 2017) - Garson, Justin
Abstract: I distinguish two forms of pluralism about biological functions, between-discipline pluralism and within-discipline pluralism. Between-discipline pluralism holds that different theories of function are appropriate for different subdisciplines of biology and psychology (for example, that the selected effects theory of function is appropriate for some branches of evolutionary biology, and the causal role theory is appropriate for disciplines such as molecular biology, neuroscience, or psychology). I provide reasons for rejecting this view. Instead, I recommend within-discipline pluralism, which emphasizes the plurality of function concepts at play within any given subdiscipline of biology and psychology. 1 Introduction 2 Different Disciplines, Different Functions 3 Two Arguments for Between-Discipline Pluralism 4 Two Objections against the Arguments for Between-Discipline Pluralism 5 A Survey of Function-Bestowing Selection Processes 6 Conclusion